Osteoreparation around the polylactide, implanted into the metadiaphys defect of the femur (experimental study) - Makarov, Vasyl; Dedukh, Ninel; Nikolchenko, Olga (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
Polylactides are synthetic materials that are X-ray-transparent, do not result in immune reactions, easy to sterilize, degrade to CO2 a nd H2O after implantation into the bone — natural products of metabolic processes. Materials based on polylactides are constantly modified in order to improve osteointegration and mechanical properties, to create a controlled degradation. Objective: to study regeneration of bone and osteointegration of polylactide in the case of implantation it into the metadiaphys defect of the rats femur. Methods: we implanted samples of polylactide with size 3×2 mm into the metadiaphys bone defect of 35 white rats. We assessed bone regeneration due to histology study with morphometry in order to define osteointegration index in 15 days, 1, 3, 6 and 9 months after the removal of the samples. Results: on the 15th day the implant was surrounded by immature bone. High index of osteointegration — 46.6 ± 1.1 was observed. Active formation of bone tissue around the implant continued up to 3 months, on the later period index of osteointegration did not change. It can testify about stopping of bone remodeling. Host bone and bone marrow were without destructive changes. On the sites of polylactide, adjacent to the bone marrow and intertrabucular spaces, cells were located directly on the implant, we did not observe any cells infringement. Signs of inflammatory process were not found. In 9 months after surgery we did not find any destruction of polylactide, index of osteointegration was 97 %. Conclusions: polyplactide implants are characterized by low rate of resorption, high osteoconductive and osteointegrative properties, biocompatibility with bone.